Construction and Interpretation of Production and Market Metrics Used to Understand Relationships with Dietary Diversity of Rural Smallholder Farming Households - Eric O. Verger; Cédric Gaillard; Andrew D. Jones; Roseline Remans; Gina Kennedy (Agriculture, 2021)
Indicators of agricultural production diversity and market access and/or participation have often been used to try to understand how agricultural production and markets influence dietary diversity of rural smallholder households. Based on a standardized search strategy, 37 studies investigating the association between an indicator of agricultural production diversity and any indicator of dietary diversity were reviewed. The characteristics of the indicators of agricultural production diversity, as well as indicators of market access and/or participation, were assessed. This review demonstrated the wide range of indicators; four types and 14 subtypes of indicators of agricultural production diversity were found in the 37 studies, and three types and 14 subtypes of indicators of market access and/or participation were found in 25 studies. While diversity of measurement ideas allows flexibility, it precludes comparability with other studies and might make it difficult to build a robust body of evidence of the impact of agriculture at farm household level on food security, diet, and nutrition.